Long-term outcome of resection of large hepatocellular carcinoma - X-P Chen; F-Z Qiu; Z. D. Wu; ZW Zhang; Z-Y Huang; Yen‐Fu Chen (2006)
Abstract Background The role of hepatectomy in the treatment of large hepatocellular carcinoma (HCC) is still controversial. This retrospective study evaluated whether the long-term outcome of hepatectomy for large HCC improved over 14 years in one centre. Methods Data from 2102 patients who underwent hepatectomy for large HCC were collected prospectively and divided into two time intervals for analysis: before end of December 1996 (group 1) and after December 1996 (group 2). Clinicopathological data for the two groups were compared, and factors associated with long-term prognosis were further analysed. Results Cumulative 1-, 3- and 5-year overall survival rates were 71·2, 58·8 and 38·7 per cent respectively in group 2, and were significantly better than respective rates of 67·8, 50·7 and 27·9 per cent in group 1. Cumulative 1-, 3- and 5-year disease-free survival rates were 61·5, 38·6 and 23·8 per cent respectively in group 2, and 56·5, 34·7 and 18·9 per cent in group 1. There was a significant difference in median survival time after recurrence between groups 2 and 1 (17 and 10 months respectively; P = 0·043). Conclusion Hepatic resection in patients with large HCC has improved overall and disease-free survival during the past decade at this institute. Long-term survival can be improved significantly by aggressive treatment of recurrent tumours.